2015
DOI: 10.1364/oe.23.032035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of substrate characteristics on performance of large area plasmonic photoconductive emitters

Abstract: We present a comprehensive analysis of terahertz radiation from large area plasmonic photoconductive emitters in relation with characteristics of device substrate. Specifically, we investigate the radiation properties of large area plasmonic photoconductive emitters fabricated on GaAs substrates that exhibit short carrier lifetimes through low-temperature substrate growth and through epitaxially embedded rare-earth arsenide (ErAs and LuAs) nanoparticles in superlattice structures. Our analysis indicates that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 35 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…11,12 Suitable photoconductive materials for photomixing must exhibit high dark resistivities, high carrier mobilities, and short carrier lifetimes. 13 Early and current photomixer work focused primarily on low-temperature-grown (LTG) GaAs 14 or superlattices of epitaxially-embedded self-assembled nanoparticles of ErAs [15][16][17] and LuAs [18][19][20] in GaAs. Development of fast photoconductive materials with smaller bandgaps, such as In 0.53 Ga 0.47 As, would benefit greatly from the mature telecommunication component infrastructure available at 1550 nm.…”
mentioning
confidence: 99%
“…11,12 Suitable photoconductive materials for photomixing must exhibit high dark resistivities, high carrier mobilities, and short carrier lifetimes. 13 Early and current photomixer work focused primarily on low-temperature-grown (LTG) GaAs 14 or superlattices of epitaxially-embedded self-assembled nanoparticles of ErAs [15][16][17] and LuAs [18][19][20] in GaAs. Development of fast photoconductive materials with smaller bandgaps, such as In 0.53 Ga 0.47 As, would benefit greatly from the mature telecommunication component infrastructure available at 1550 nm.…”
mentioning
confidence: 99%
“…To demonstrate the superior performance of the presented terahertz source, a plasmonic terahertz nanoantenna array is fabricated on a low-temperature-grown GaAs (LT-GaAs) substrate with a carrier lifetime of 0.3 ps 26 . The same device area, the same ratio between the active and shadowed areas, and the same nanoantenna length are chosen for this device to ensure a fair comparison.…”
Section: Resultsmentioning
confidence: 99%
“…[170][171][172][173] A radiation power of 3.8 mW over the 0.1-to 5-THz range of frequency was demonstrated through this architecture. 174 As of 2017, the best signal to noise ratio achieved for THz TDS using this architecture was reported to be 107 dB over the 0.1-to 4-THz range of frequency. 175 In 2019, a multinational research consortium from the United States, Russia, and Japan reported that current-voltage measurements under femtosecond laser illumination show an increase of the transient photocurrent of 15 times higher than that of conventional photoconductive antennas.…”
Section: Novel Terahertz Photoconductive Antennas With Higher Photon mentioning
confidence: 93%